Surgical corrections of long ureteral defects (initial experience) - Zhaksylyk Doskaliyev; Talgat Kurmanov; Ulanbek Zhanbyrbekuly; Adilbek Mukazhanov; Dauren Mustafinov; Aigerim Bekenova (National Scientific Medical Center, 2022)
Introduction: Restoration of patency of ureters with long defects is one of the major problems in urology. There are cases when it is impossible to perform plastic surgery of ureter with own tissues or bladder; in these situations, appendicoureteroplasty or kidney autotransplantation can be promising solutions. Material and methods: 4 patients underwent surgical corrections or ureter strictures: two underwent appendicoureteroplasty and two - kidney autotransplantation. To verify the diagnosis of long ureteral defects, standard research methods were used: ante- and retrograde pyeloureterography. Results and discussion: In the early postoperative period, all patients underwent dynamic ultrasonography of the abdominal cavity and retroperitoneal space; in addition, hemodynamics parameters as well as clinical and biochemical laboratory blood parameters were monitored. The early postoperative period in three patients proceeded with no incidents and did not require serious additional studies. In one patient after appendicoureteroplasty dynamic intestinal obstruction developed on the third day post-op, which was resolved conservatively. In the late postoperative period the condition of the patients was satisfactory. There are few articles describing surgical interventions that can treat long ureteral defects, with appendiculoplasty and kidney autotransplantation being the most effective. However, each procedure has own advantages and disadvantages, as well as risks. Conclusion: In our study, we performed these two methods with two patients for each method. Results are promising, but for a better statistical analysis and more thorough follow-up we need more patients for both appendiculoplasty and kidney autotransplantation.